Portfolio Selection using Cointegration and Modern Portfolio Theory: An Application to the Colombo Stock Exchange (MATEMATIKA, 2013)
Profitable stock market investments have never been easy due to the lack of predictability and higher risk of stock returns. Hence the necessity of portfolio selection has arisen in order to find the ideal portfolio which best suits the stock market behavior. This study aims at devising the ideal sector portfolio and identifying a better strategy for developing the ideal sector portfolio in the Colombo Stock Exchange (CSE). It covers a period when CSE was one of the best performing stock exchanges in the world; the post civil war period in Sri Lanka. In this study better portfolios were derived from two strategies: (1) Cointegration approach; and (2) Modern Portfolio Theory (including Capital Market Theory) where both are widely used to derive portfolios related to stock market trading. Then the performances of the better portfolios derived were compared by means of the Sharpe Ratio, Information Ratio, Return and Risk in order to determine the ideal portfolio as well as the better strategy. Final conclusion of the study states that “Market portfolio” obtained from the Modern Portfolio Theory performs better than “Best Cointegrated portfolio” obtained from the Cointegration approach in the considered period of time by dominating most of the comparison measures. Also the ideal portfolio consisted of eight sectors out of twenty sectors in CSE with varying weight percentages. Further the best portfolio selection method between the two strategies could have been obtained regardless the period if the methodology is implemented for several Stock Exchanges. However, limitations in accessing necessary data prevented this implementation in the study. Keywords: Sharpe Ratio; Information Ratio; Cointegration; Modern Portfolio Theory; Capital Market Theory; Colombo Stock Exchange. 2010 Mathematics Subject Classification: 62P20